2016
DOI: 10.1016/j.physbeh.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-related changes in between-network connectivity in overweight/obese adults

Abstract: Understanding how exercise affects communication across the brain in overweight/obese individuals may provide insight into mechanisms of weight loss and maintenance. In the current study, we examined the effects of a 6-month exercise program in 11 overweight/obese individuals (mean BMI: 33.6±1.4 mg/kg2; mean age: 38.2±3.2 years) on integrative brain “hubs,” which are areas with high levels of connectivity to multiple large-scale networks thought to play an important role in multimodal integration among brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 73 publications
1
9
1
Order By: Relevance
“…Concerning further associations of BMI and functional connectivity, only the visual network was found to be associated with higher BMI, but the extent of increased connectivity was very limited. In our large cohort, we did not observe previously reported increased putamen and insula connectivity [Hogenkamp et al, 2016], decreased insula-anterior cingulate cortex (ACC) connectivity [Moreno-Lopez et al, 2016], increased salience network connectivity [Figley et al, 2016;Garcia-Garcia et al, 2013], reduced temporal lobe network connectivity [Kullmann et al, 2012] or increased DMN connectivity [Kullmann et al, 2012;Legget et al, 2016;Tregellas et al, 2011] with higher BMI. Similar to our results, one study reported reduced precuneus connectivity for obese compared with lean participants, although the results might have been confounded by the significant age difference between groups [Geha et al, 2016].…”
Section: Functional Connectivity and Obesity In Agingcontrasting
confidence: 99%
“…Concerning further associations of BMI and functional connectivity, only the visual network was found to be associated with higher BMI, but the extent of increased connectivity was very limited. In our large cohort, we did not observe previously reported increased putamen and insula connectivity [Hogenkamp et al, 2016], decreased insula-anterior cingulate cortex (ACC) connectivity [Moreno-Lopez et al, 2016], increased salience network connectivity [Figley et al, 2016;Garcia-Garcia et al, 2013], reduced temporal lobe network connectivity [Kullmann et al, 2012] or increased DMN connectivity [Kullmann et al, 2012;Legget et al, 2016;Tregellas et al, 2011] with higher BMI. Similar to our results, one study reported reduced precuneus connectivity for obese compared with lean participants, although the results might have been confounded by the significant age difference between groups [Geha et al, 2016].…”
Section: Functional Connectivity and Obesity In Agingcontrasting
confidence: 99%
“…Two studies found a reduction in implicit wanting for high-fat relative to low-fat foods after exercise training [54,62]. This may be a result of a direct effect of exercise on brain regions related to food reward, as shown by the fMRI studies included in the current review, and others [73,74]. Furthermore, as exercise affects cognition and executive function, it has been proposed that processes such as inhibitory control could have a moderating effect on wanting and modulate eating behavior [66].…”
Section: Chronic Exercise Training Studiesmentioning
confidence: 62%
“…DMN is a network most active while processing internal mental status, such as self-referential thinking/autobiographical memory, and during external unfocused attention (Andrews-Hanna, Smallwood, & Spreng, 2014). Previous studies found that PCC activity was increased in obese/overweight individuals (Kullmann et al, 2012) and that activity in this region was reduced following chronic exercise (Legget et al, 2016). PCC activation has also been observed during presentation of visual food cues and during food tasting (DelParigi, Chen, Salbe, Reiman, & Tataranni, 2005).…”
Section: Alterations In Self-referential Regionsmentioning
confidence: 99%